Marlborough 2010: Policy Action Plan, Downtown: In Focus. - Forbes, David J.; Knoff, Adam B.; Lopez-Bernal, Gabriel J.; Petschek, Nicholas. (Tufts University. Tisch Library., 2018)
2009 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Marlborough 2010.